Níveis de diferentes linhagens de células progenitoras circulantes e da função vascular em atletas de endurance - Berger, Rebeca Caldeira Machado (2011)
Background. Recent evidence has shown that vascular function depends not only resident cells in the vessel wall but also appears to be significantly modulated by circulating cells derived from bone marrow. The physical training induces endothelial progenitor cells (EPCs) mobilization and has beneficial effects on endothelial function in the presence of vascular disease or cardiovascular risk factors. However, this effects in healthy individuals is still little known. Aims: Assess CPCs, EPCs levels and endothelial function in healthy male runners are long-term and healthy sedentary. Methods: Longterm runners (TA group, n= 38, >40km/week, For over two years with speed ≥ 15km/h), aged 21 to 58 years, were instructed not to do exercise for 24 hours before collection blood. Healthy sedentary subjects were included as controls (CT group, n= 30). All were participants in the ESCHOT study. CD34+ , CD133+ cells and CD34+CD133+ subpopulations (CPCs), CD34+KDR+ (EPCs) were quantified by flow cytometry on total pheripheral blood. The endothelial function was assessed by flow-mediated dilatation (FMD) of brachial artery using high resolution vascular ultrasound. Data not normally distributed were analyzed by testing Mann Whitney U and Spearman’s correlation coefficient (r), expressed an median ± standard error of mean. Data with normal distribution were analyzed by T test and Pearson's correlation coefficient, expressed as mean ± standard error of mean. The p value < 0,05 was considered significant. Results: There were no statistical difference between groups in the count of CPCs. (CT: CD34+ : 0,0381 ± 0,0036; CD133+ : 0,0308 ± 0,0043; CD34+ /CD133+ : 0,0149 ± 0,0024. TA: CD34+ : 0,0399 ± 0,0050; CD133+ : 0,0199 ± 0,0052; CD34+ /CD133+ : 0,0124 ± 0,0033). Showed higher levels of EPCs in the TA group (CD34+KDR+ : 0,0121 ± 0,0025) compared to CT group (0,0083 ± 0,0012) with a trend towards statistical significance (p = 0,057). The% FMD in the TA group (8.71 ± 0.59) was similar to CT (7.61 ± 0.59) and did not correlate with the number of EPCs.Conclusion: Among the populations evaluated, only the levels of EPCs were higher in TA compared to CT, which was not correlated with improved endothelial function. This finding may be associated with the studied population be of healthy individuals without the presence of factors associated with endothelial dysfunction.